Continuous planting Eucalyptus plantations in subtropical China: Soil phenolic acid accumulation and adsorption physiognomies - Ullah, Saif; Xu, Yuanyuan; Liao, Chengrui; Li, Wannian; Cheng, Fei; Ye, Shaoming; Yang, Mei (Frontiers in Forests and Global Change, 2023)
As phenolic acids accumulated in monocropping plantations, their allelopathic effects caused the soil's fertility to decline and productivity to decrease. The effects of stand age and generational turnover of phenolic acids in soil remain unclear. This study examined the variations in phenolic acids in soils from Eucalyptus plantations to determine the variations in planting years and generations. Their accumulation characteristics were discussed to assess if they would increase over time. Soils were collected from three Eucalyptus plantations: a 6-year-old first-generation plantation (6a1g), 9-year-old first-generation plantation (9a1g) and 6-year-old second-generation plantation (6a2g). Seven phenolic acids were identified from different soil samples by high-performance liquid chromatography. In addition, exogenous phenolic acids were added to the soil samples to study the kinetics as well as the adsorption and desorption characteristics of soils. The total of seven phenolic compounds of 6a1g (38.451 μg•g−1) was higher than the 9a1g and 6a2g soils, the total of 6a2g (27.257 μg•g−1) was higher than the 9a1g (15.536 μg•g−1). In the tested soil, the p-hydroxybenzoic acid accounted for 51.6% (for 6a1g), 51.1% (for 9a1g) and 33.5% (for 6a2g) of the total amount of the seven phenolic acids, the p-hydroxybenzoic may have had higher allelopathic capacity in these Eucalyptus plantation soils. Soil bulk density showed a strong positive correlation with vanillic, ferulic, cinnamic acids and total content, and SOM also had an extremely positive correlation with p-hydroxybenzoic, coumalic acids and the total. The pseudo-second-order model can be used to describe the kinetic adsorption better than the other two models. The Freundlich model could fit the desorption isotherms better than the adsorption isotherms. The 6a1g plantation had the highest total content, adsorption rate, and desorption capacity of phenolic acids among the different Eucalyptus plantation soils. The best model to describe kinetic adsorption for the seven phenolic acids in different types of soils was the pseudo-second-order kinetic. Finally, the tested phenolic acids were not accumulated in the soils of first and second generation Eucalyptus plantations.